New oxygen isotope evidence for long-term Cretaceous climatic change in the Southern Hemisphere - Clarke, L; Jenkyns, H (1999)
A new composite δ18O record, generated from calcareous fine-fraction and bulk sediments from the Exmouth Plateau, details long-term Cretaceous climatic change at mid-latitudes in the Southern Hemisphere. Assessment of new and previously published δ18O data indicates that a mid-Cretaceous global climatic optimum was achieved sometime between the time of the Cenomanian-Turonian boundary and the middle Turonian, when surface-ocean paleotemperatures were the highest of the past 115 m.y. Periods of cooling and warming that reversed the general patterns were superimposed on long-term Aptian-Turonian warming and Turonian-Maastrichtian cooling trends, respectively. Extrapolation of Southern Hemisphere paleotemperature trends to Maastrichtian paleotemperature data from a low-latitude Pacific guyot implies that maximum mid-Cretaceous low-latitude paleotemperatures could have been in excess of 33 °C.